Ultrafast magnetic resonance imaging for iron quantification in thalassemia participants in the developing world: The TIC-TOC Study (Thailand and UK International Collaboration in Thalassaemia Optimising Ultrafast CMR). - Abdel-Gadir, A; Vorasettakarnkij, Y; Ngamkasem, H; Nordin, S; Ako, E; Tumkosit, M; Sucharitchan, P; Uaprasert, N; Kellman, P; Piechnik, S; Fontana, M; Fernandes, J; et al. (American Heart Association, 2016)
Thalassemia is the most common monogenetic disorder worldwide, with 60 000 infants with thalassemia major born annually.1 Survival often depends on regular blood transfusions to correct anemia and to reduce ineffective erythropoiesis, but these transfusions can result in iron overload and organ failure unless chelation therapy is undertaken. Serum ferritin levels continue to be used as a guide to chelation but are unreliable, and the availability of cardiovascular magnetic resonance (CMR) T2* imaging has transformed patient management by allowing organ-specific quantification of iron content. Countries with a high prevalence of thalassemia major have CMR, but magnet time is expensive and analytic expertise lacking. The aim of TIC-TOC (Thailand and UK International Collaboration in Thalassaemia Optimising Ultrafast CMR) was to investigate whether ultrafast CMR mapping could provide reliable immediate diagnoses of heart and liver iron content, eliminating the need for complex analysis, thus reducing costs to a level within local resources. The research received approval by the Institutional Review Board of the Faculty of Medicine at Chulalongkorn University. All participants provided written informed consent.